LEVEL OF STRESS AND ITS RELATION TO BLOOD PRESSURE SERVERS OF THE CAMPUS ALTAMIRA IFPA-PA (Fiep Bulletin - online, 2012)
This study is characterized as a descriptive study whose objective was to analyze the profile of Stress and its relationship with the PA servers Federal Institute of Para As a focus aimed at identifying the level of stress and pressure of the servers and relate them. The study sample consisted of twenty-four (N = 24) of the Federal Institute servers, and in relation to gender, we used both. As an instrument of measurement, we used a anmenese (1989), protocol through the questionnaire Why Managers Burn Out, and the data were collected on the campus of Altamira / PA. As the result, since the stress level was presented as normal predominance of about 63% since the beginning was marked with about 33% and the stress was already installed with 4% and for PA-characterized with some 80% normal and high normal BP, which is characterized in "
Keywords: Stress; Blood Pressure; federal officials